2017
DOI: 10.1093/ecco-jcc/jjx147
|View full text |Cite
|
Sign up to set email alerts
|

The Proton-activated Receptor GPR4 Modulates Intestinal Inflammation

Abstract: Absence of GPR4 ameliorates colitis in IBD animal models, indicating an important regulatory role in mucosal inflammation, thus providing a new link between tissue pH and the immune system. Therapeutic inhibition of GPR4 may be beneficial for the treatment of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 40 publications
5
98
0
Order By: Relevance
“…In contrast with mice in the IL‐10 −/− group, IL‐10 −/− mice were protected from colonic mucosa inflammation with less infiltration of inflammatory cells, lower mean inflammation scores, and a partially restored glandular and goblet cell architecture by MF treatment (Figure B and C). Subsequently, we detected the colonic MPO concentration, which is now widely accepted as a marker to quantify the degree of the accumulation of inflammatory cells, especially neutrophils . Notably, increased concentrations of MPO in IL‐10 −/− mice were reduced by MF treatment (Figure D).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast with mice in the IL‐10 −/− group, IL‐10 −/− mice were protected from colonic mucosa inflammation with less infiltration of inflammatory cells, lower mean inflammation scores, and a partially restored glandular and goblet cell architecture by MF treatment (Figure B and C). Subsequently, we detected the colonic MPO concentration, which is now widely accepted as a marker to quantify the degree of the accumulation of inflammatory cells, especially neutrophils . Notably, increased concentrations of MPO in IL‐10 −/− mice were reduced by MF treatment (Figure D).…”
Section: Resultsmentioning
confidence: 97%
“…Subsequently, we detected the colonic MPO concentration, which is now widely accepted as a marker to quantify the degree of the accumulation of inflammatory cells, especially neutrophils. 15 Notably, increased concentrations of MPO in IL-10 −/− mice were reduced by MF treatment ( Figure 1D). It has been shown that chronic inflammation in the colon of IL-10 −/− mice is mainly mediated by Th1 and Th17 cells.…”
Section: Mf Treatment Reduced Weight Loss Typically Associated With Cmentioning
confidence: 92%
See 1 more Smart Citation
“…One such family of GPCRs are the protonsensing GPCRs, which consist of GPR4, GPR65 (TDAG8), and GPR68 (OGR1) (Justus et al, 2013;Justus et al, 2017;Ludwig et al, 2003;Sanderlin et al, 2015). These receptors have been implicated in the modulation of intestinal inflammation (de Valliere et al, 2015;Lassen et al, 2016;Sanderlin et al, 2017;Wang et al, 2018). Studies have shown GPR4 is responsible for acidosis-induced endothelial cell inflammation and can functionally increase leukocyte adhesion with endothelial cells (Chen et al, 2011;Dong et al, 2017;Dong et al, 2013;Tobo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown GPR4 is responsible for acidosis-induced endothelial cell inflammation and can functionally increase leukocyte adhesion with endothelial cells (Chen et al, 2011;Dong et al, 2017;Dong et al, 2013;Tobo et al, 2015). GPR4 genetic deletion in mice reduces intestinal inflammation and mucosal leukocyte infiltration in both inducible and spontaneous colitis mouse models Wang et al, 2018). However, the effects of pharmacological modulators of protonsensing GPCRs in intestinal inflammation have not been investigated.…”
Section: Introductionmentioning
confidence: 99%